Development and verification of mathematical models for reinforced concrete encased wide-flanged steel columns exposed to fire [microfilm] - Hishamuddin Alham (Skudai : Universiti Teknologi Malaysia, 2000)
Thesis (Doctor of Philosophy) - Universiti Teknologi Malaysia, 2000